PERANCANGAN PADUAN SHALAT DALAM BENTUK MEDIA INTERAKTIF - Stefvany Stefvany (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2019)
The high development of knowledge and technology, especially in computer. Nowadays, the most media that are commonly used to learn how to shalat and it’s doa is book that included picture, even there is so many guide books to shalat, the willingness to shalat for children are still under- expectation. The previous learning media is ineffectiveTherefore, we will make learning media as interactive media which include the guide to shalat for children to learn about more interactive guide to shalat that more interested than it’s visual and to increase children’s interest to shalat. In this research, writers use SWOT analysis method.Using this analysis method, the result will be interactive media that will be applied toelectronic media such as computer and laptop. That will be title as “Yuk Belajar Shalat bersama Calief dan Ara”. This media will also provide using Poster, Flayer, X-Banner, Key Chain, Sticker, Mousepad, Coloring Book and Shalat Wears.Keywords: Prayer Guide, Interactive Media.